Brazilian knowledge on artisanal fishing: state of the question (PerCursos, 2023)
Artisanal fishing and quilombos are part of the universe of 28 socioeconomic and cultural activities that make up traditional Brazilian communities. We seek in this article to identify the following state of the question: which were the themes, the subjects of the research, where the researched communities are situated and which were the concepts used to understand the themes of academic studies on artisanal fishing related to quilombos and traditional communities? The analyzed data were obtained from the abstracts of postgraduate studies, that take part of the Catalog of Theses and Dissertations of CAPES, where we identified 368 studies resulting from searches such as “artisanal fishing AND quilombola” (40) and “artisanal fishing AND traditional communities” (328 ). In view of this universe, we are interested in analyzing a scope of 70 studies conducted between 2012 and 2021, divided into two major areas of knowledge: multidisciplinary and human sciences. After using defined selection and discard criteria, the final thematic cut that constitutes a corpus of analysis of the present study was formed by 17 studies: four theses and 13 dissertations. As a result of this analysis, the identification of seven quilombola communities, five traditional artisanal fishing communities, four case studies and 67 concepts/group of concepts worked in 13 areas of scientific knowledge: Anthropology, Social Sciences, Education, Education and Contemporaneity, Education and Culture, Languages and Representations, Cognition and Language, Social Development, Environmental Law and Public Policies, Public Policies, Strategies and Development, Social Policies and Political Sociology.
Keywords: artisanal fishing; quilombola; traditional communities